2011
DOI: 10.1063/1.3569489
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in fluctuation theorems and free energy recovery

Abstract: Abstract. In this note we review recent progress about fluctuation relations and their applicability to free energy recovery in single molecule experiments. We underline the importance of the operational definition for the mechanical work and the non-invariance of fluctuation relations under Galilean transformations, both aspects currently amenable to experimental test. Finally we describe a generalization of the Crooks fluctuation relation useful to recover free energies of partially equilibrated states and t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 56 publications
(27 reference statements)
0
19
0
Order By: Relevance
“…It takes little effort to verify that equations (2.5)-(2.7) hold exactly for standard classical ergodic Hamiltonian systems with an arbitrary number of degrees of freedom N. Similarly, the canonical ensemble discussed below can be applied to (sub)systems of any size. These mathematical facts are widely appreciated by many colleagues [9,[12][13][14][15]18,19,21]-in particular those interested in understanding DNA folding [24], microscopic information storage and erasure [25] and fluctuation phenomena [26]-and yet remain ignored by a few others [23,27]. When judged objectively, there is no doubt that the application of thermodynamic concepts to finite systems has considerably advanced our understanding of biophysical, colloidal and quantum processes.…”
Section: (B) Positive and Negative Temperatures: An Examplementioning
confidence: 99%
“…It takes little effort to verify that equations (2.5)-(2.7) hold exactly for standard classical ergodic Hamiltonian systems with an arbitrary number of degrees of freedom N. Similarly, the canonical ensemble discussed below can be applied to (sub)systems of any size. These mathematical facts are widely appreciated by many colleagues [9,[12][13][14][15]18,19,21]-in particular those interested in understanding DNA folding [24], microscopic information storage and erasure [25] and fluctuation phenomena [26]-and yet remain ignored by a few others [23,27]. When judged objectively, there is no doubt that the application of thermodynamic concepts to finite systems has considerably advanced our understanding of biophysical, colloidal and quantum processes.…”
Section: (B) Positive and Negative Temperatures: An Examplementioning
confidence: 99%
“…1 -2012/6/7 -19:43 -page 2 2 ten years has shown that FRs hold for a great variety of systems thus featuring one of the rare statistical physical principles that is valid even very far from equilibrium: see summaries in [13,14,15,16,17,18] for stochastic processes, [19,20,21,22,23,24] for deterministic dynamics and [25,26] for quantum systems. Many of these relations have meanwhile been verified in experiments on small systems, i.e., systems on molecular scales featuring only a limited number of relevant degrees of freedom [27,28,29,30,31,32], cf. the Chapters by Ciliberto et al, Alemany et al, and Sagawa and Ueda.…”
Section: Introductionmentioning
confidence: 99%
“…Our aim is to derive the optimal control strategy over the class of smooth potential forces for the problem adapted to the Second Law of Thermodynamics. From the experimental slant, smooth potentials model macroscopic degrees of freedom of the system whose state is determined by external sources [16]. We show that our problem is well-posed when regarded as the limit of a more general control problem which takes into account the energy cost of the control.…”
mentioning
confidence: 93%